Gender, Class and Power Struggle: A Content Analysis of Selected Pakistani Dramas (Journal of Asian Development Studies, 2025)
Through their fashion input and their effect on social attitudes and behavioural patterns along with their impact on group thinking dramas modify the cultural standards of society. The subtle approach of these influences reaches audiences while delivering messages that may exist consciously but also unconsciously within their content. Elements within the content determine whether this impact will be positive or negative. The Pakistani television entertainment industry has incorporated local Pakistani themes into family political storylines which gained popularity from the foreign content. The research on dramas based on foreign content and family political elements in Pakistani serials exists but there needs to be more investigation regarding how gender roles get portrayed within social class hierarchies and their accompanying power systems. The investigation needs to move forward to determine how foreign influence affects content changes and how patriarchy both shapes and is shaped by drama storytelling. This research shows how Pakistani television shows both foster and reshape accepted social standards about gender relationships as well as social status and power dynamics. The researchers conducted quantitative content analysis on four specific dramas to answer the research questions. The method allows researchers to learn about audience views concerning gender issues and class distinctions as well as power relations across different economic levels. The research data demonstrates that media presentations of power disputes alongside gender relationships and social status dynamics showcase simultaneous acceptance and critique of sociocultural standards.